Toll-like receptor 3 gene regulates cataract-related mechanisms via the Jagged-1/Notch signaling pathway. Issue 6 (1st June 2022) - Xie, Weiwei; Yu, Qihua; Wang, Layi; Shao, Yongqing; Bo, Qingyun; Wu, Guohai
ABSTRACT: Epithelial-melancholy transition (EMT) is the main cause of organ fibrosis and a common pathogenetic mechanism in most cataracts. This study aimed to explore the molecular mechanism of Toll-like receptor (TLR)-3 in the occurrence and development of post-cataract EMT and to provide new ideas for the prevention and treatment of posterior capsule opacification (PCO). In the presence or absence of TLR3, the human lens epithelial cell (LEC) line, SRA01/04, was treated with the transforming growth factor (TGF)-β2. Cell counting kit-8 (CCK-8) and Transwell assays were used to analyze the cell proliferation, migration, and invasion. The expression levels of proteins and RNAs were detected by western blotting and quantitative polymerase chain reaction (qPCR) experiments. Functional gain and loss studies showed that TLR3 regulates the proliferation, migration, and invasion of LECs and EMT induced by TGF-β2. Moreover, TLR3 regulates the expression of Jagged-1, Notch-1, and Notch-3 These findings indicate that TLR3 prevents the progression of lens fibrosis by targeting the Jagged-1/Notch signaling pathway to regulate the proliferation, migration, and invasion of LECs, and TGF-β2-induced EMT. Therefore, the TLR3-Jagged-1/Notch signaling axis may be a potential therapeutic target for the treatment of fibrotic cataracts. GRAPHICAL ABSTRACT: uf0001